Small ruminant production in the humid tropics - Haan, Cees de; Westley, S.; Chater, S. (International Livestock Centre for Africa, 1979)
Research review on sheep and goat production in the humid zone of West Africa, w. respect to animal population, production parameters, reproduction, forage production, supplementary feeding based on agro - industrial byproducts, disease incidence, particularly peste petits ruminants & helminthiasis, housing, and economic aspects of small and large scale production, w. proposals for further research.